Rancang Bangun Prototype Sistem Monitoring dan Data Logger pada Sistem Listrik 3-Phase - Arif Febriansyah Juwito; Diono Diono; Miftahul Jihad (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Negeri Batam, 2022)
Electrical energy is one of the basic needs in life today, but in its utilization, several problems can cause losses in the electricity system, one of the causes is nontechnical shrinkage that often occurs on the customer's side in the form of electricity theft. Therefore, innovation is carried out using IoT (Internet of Things) in order to easily monitor the parameters of electricity magnitude. In this study, a stage of collecting parameters of the amount of electricity was proposed. The electric power observation method uses a voltage sensor (ZMPT101B) and a current sensor (SCT-013-000). Arduino Nano microcontrollers are used in measurement systems and the Wemos D1 Mini is used as a link to internet connections over Wi-Fi networks. Measurement data is sent and stored to the MySQL Database in the form of a data logger. The media used is a Website-based GUI. The results showed that remote monitoring using GUI can be done, where this tool can send parameters measuring the amount of electrical voltage, current, active power, and power factor as well as calculations of energy consumption and electricity usage costs to the GUI with a period of once every 10 minutes.